The prevalence of transfusion-transmitted infections and nucleic acid testing among blood donors in Majmaah, Saudi Arabia - Mohammed Alaidarous; Ranjay K. Choudhary; Mohamed I. Waly; Shabir Mir; Abdulaziz Bin Dukhyil; Saeed S. Banawas; Bader M. Alshehri (Elsevier, 2018)
Background: Few studies discussed the prevalence of TTIs in Saudi donor blood samples. Thus, this study investigated the prevalence of hepatitis B virus (HBV), hepatitis C virus (HCV), human immunodeficiency virus (HIV), human T-lymphotropic virus (HTLV), syphilis and malaria in such samples to determine the efficacy of conducting serological and NATs on blood donors at King Khalid General Hospital in Majmaah, Saudi Arabia. Methods: A total of 3028 donated blood units were collected from August 2015 to March 2017. Serum samples were screened for hepatitis B surface antigens (HBsAgs), HBsAbs, total anti-core antibodies (HBcAbs), HCV antigens and HIV Ab/Ag combinations. Additionally, plasma was screened for syphilis (TPHA) and HTLV. Samples were also tested for malaria with rapid malaria antigen tests. Finally, NATs were performed for the simultaneous direct detection of HBV, HCV and HIV in each sample. Results: Out of the 3028 blood samples, 10 (0.33%) reacted to HBsAgs; 12 (0.40%) reacted to HCV antigens; 4 (0.13%) reacted to HIV Ab/Ag combinations; 6 (0.20%) reacted to HTLV antibodies; 297 (9.81%) reacted to HBcAbs and 236 (7.80%) reacted to HBsAbs. Additionally, NATs showed that 14 (0.46%) reacted to NAT-HBV; 20 (0.66%) samples were reacted to NAT-HCV and 2 (0.07%) samples reacted to NAT-HIV. Finally, 16 (0.53%) were positive for syphilis. No samples were positive for malaria. Conclusions: The results indicated that NATs are more effective than serology tests for detecting TTIs. Moreover, correlations between standard serology tests and NATs indicated that using NATs could improve test sensitivities and decrease residual risks of TTIs and ensure safe blood transfusions. Keywords: Transfusion-transmitted infections, Nucleic acid testing, Seroprevalence, Blood transfusion, Majmaah